NASIONALISME PUITIS: NASIONALISME DAN BUDAYA KONSUMEN - Faruk F (Faculty of Humanities, Jember University, 2013)
The Indonesian nationalism has emerged through a long process of colonialism opression. In the course of history, it experienced a significant change. The dynasty politics, novel and newspaper, and religion became major sources of the handing down of nationalist values that rooted in the past. They provide inspirations for men of letters, poets, drama and art workers to immortilize various historical events in Indonesia. Recent development demonstrates a phenomenon of the truncated, superficial, and local nationalism. Solidarity for the victims of natural disasters, the oppressed people, football fans club solidarity, and solidarity for Ambalat, Simpadan, Palestine, Afghanistan, have proved the trend. Poetical experiences as an aesthetical appreciation tend to reject repetition. Therefore, the same spirit tends not to be brought to face similar phenomena because of boredom and saturation.Keywords: consumer culture, nationalism, repetition rejection, poetic, superficial